2017
DOI: 10.1002/ptr.5978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of quercetin treatment on CYP2C9 enzyme activity of diclofenac in healthy human volunteers

Abstract: The purpose of present study was to evaluate the effect of quercetin on pharmacokinetics of diclofenac sodium (DIC) in healthy volunteers. The open-label, 2 period, sequential study was conducted in 12 healthy volunteers. DIC 100 mg was administered during control and after quercetin phases. Quercetin 500 mg was administered twice daily for 10 days during quercetin phase. Treatment with quercetin significantly enhanced maximum plasma concentration (C ) area under the curve (AUC ), and half life, while signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Nevertheless, a milder inhibition regarding CYP2C19-and/or CYP3A4-mediated elimination of certain drugs cannot be excluded, since not only Q but its metabolites can also exert moderate inhibition on these enzymes. This hypothesis is supported by the report of Bedada and Neerati [67] where the administered Q (500 mg twice daily for 10 days) significantly decreased the CYP2C9-mediated elimination of diclofenac in healthy human subjects, despite the observations in a previous in vitro study that Q and some of its conjugates (Q3 S, IR, and tamarixetin) were only weak inhibitors of the enzyme and glucuronides (Q3G and I3G) did not affect CYP2C9 activity [14]. Previous studies showed the similar or stronger interactions of methyl and sulfate metabolites of Q with xanthine oxidase enzyme [68] and human serum albumin [14,69] compared to the parent compound.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, a milder inhibition regarding CYP2C19-and/or CYP3A4-mediated elimination of certain drugs cannot be excluded, since not only Q but its metabolites can also exert moderate inhibition on these enzymes. This hypothesis is supported by the report of Bedada and Neerati [67] where the administered Q (500 mg twice daily for 10 days) significantly decreased the CYP2C9-mediated elimination of diclofenac in healthy human subjects, despite the observations in a previous in vitro study that Q and some of its conjugates (Q3 S, IR, and tamarixetin) were only weak inhibitors of the enzyme and glucuronides (Q3G and I3G) did not affect CYP2C9 activity [14]. Previous studies showed the similar or stronger interactions of methyl and sulfate metabolites of Q with xanthine oxidase enzyme [68] and human serum albumin [14,69] compared to the parent compound.…”
Section: Discussionsupporting
confidence: 87%
“…In the same model applied in this study, casticin was 1.3-fold weaker, while diosmetin was 2.7-fold stronger inhibitor of CYP2C9 enzyme compared to DHF [26,29]. Despite the fact that quercetin and its metabolites proved to be weak inhibitors of CYP2C9-catalyzed diclofenac hydroxylation [25], quercetin (500 mg, administered twice daily) significantly inhibited the metabolism of diclofenac in healthy human volunteers [43]. These observations suggest the potential hazardous consequences of the simultaneous administration of DHF with certain drugs eliminated through CYP2C9.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been reported, flavonoids and their conjugated metabolites interact with serum albumin [5,43,44] and with several biotransformation enzymes [45][46][47][48]. Flavonoids and their conjugated metabolites reach only nanomolar or low micromolar systemic plasma concentrations [49], in contrast to some of the colonic flavonoid metabolites [27].…”
Section: Discussionmentioning
confidence: 95%